Digital Power and the Regime of Truth: A Foucauldian Analysis of Algorithmic Journalism - Henry Sianipar; Hermawan Yulianto; Hasan Mukti Iskandar; Alexander Seran (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
Algorithmic journalism has transformed the Indonesian digital media landscape, creating a paradox between the democratization of information and the restriction of freedom. This study analyzes the phenomenon through the lens of Michel Foucault's theory of power, using a qualitative research method with a critical constructionism paradigm. The study of platforms such as Detik.com, TikTok, and Facebook reveals that algorithms operate as a “digital panopticon,” monitoring and disciplining user behavior through biopower technology. Filter bubbles and algorithmic bias create a “regime of truth” that shapes digital subjectivity and controls the distribution of information. However, Foucault's concept of parrhesia offers strategies of resistance through digital literacy and self-management practices. This research contributes to understanding algorithms not as neutral technical instruments but as power mechanisms that shape digital social reality. The practical implications include developing algorithmic transparency regulations and strengthening public participation in technology oversight.